Antecedents of Impression Management Use and Effectiveness in a Structured Interview† - Van Iddekinge, Chad H.; McFarland, Lynn A.; Raymark, Patrick H. (Journal of Management, 2007)
The authors examine personality variables and interview format as potential antecedents of impression management (IM) behaviors in simulated selection interviews. The means by which these variables affect ratings of interview performance is also investigated. The altruism facet of agreeableness predicted defensive IM behaviors, the vulnerability facet of emotional stability predicted self- and other-focused behaviors, and interview format (behavior description vs. situational questions) predicted self-focused and defensive behaviors. Consistent with theory and research on situational strength, antecedent—IM relations were consistently weaker in a strong situation in which interviewees had an incentive to manage their impressions. There was also evidence that IM partially mediated the effects of personality and interview format on interview performance in the weak situation.